KONSEP DEBAT (JADAL) DALAM AL-QUR’AN URGENSI KECERDASAN DAN MORALITAS - Zahratunnisa', Zahratunnisa' (Academic Journal of Islamic Principles and Philosophy, 2022)
The concept of debate (Jadal) of the Qur'an in its study is full of the urgency of aspects that must be possessed, namely intelligence and morality. Accommodating human nature which tends to be a lot of debate and questions, the Qur'an provides examples, methods, and ways to deal with opponents. The significant nature of the Qur'anic debate is without complicated theories, but sometimes it also resembles a philosophical way of thinking while remaining elegant and on target. But of course, because the Science of Kalam is not a revelation, it is unlike the perfection of Al-Quran. This paper tries to present the problems surrounding the Jadal or debate of the Qur'an and the values contained in it, which can be taken as ibrah or lessons about the height of a civilization. Using the descriptive-qualitative method of literature, this research results that the Qur'anic debate is based on the truth, with simple and complex styles according to human capacities that are stratified, and still fascinates with elegant ethics when dealing with the opponents.